(untitled) (Research, Society and Development, 2020)
Objectives: to verify the fulfillment of the fourth and fifth steps of the Baby-Friendly Hospital Initiative in a reference maternity hospital in northeastern Brazil. Methodology: Descriptive research of quantitative nature, conducted between March and July 2019, with 380 puerperal women interviewed in the hospital wards to fill out a form. The data were tabulated according to absolute and relative frequencies. Results: It was found that 17% of the babies were placed to breastfeed in the delivery room in fulfillment of the fourth step of the Baby-Friendly Hospital Initiative, 82% of the mothers received help to breastfeed in fulfillment of the fifth step; 79% of mothers were between 20 and 30 years old, 61% were mixed, 71% were married, 57% attended high school, 69% were housewives, 48% with income between 1 and 2 minimum wages, 42% had 2 children, 54% did not have their own residence, all had prenatal care, 66% had more than 6 consultations, 79% was oriented about breastfeeding. Conclusion: The indexes found for the fourth and fifth steps of the Baby-Friendly Hospital Initiative are below those recommended by the Ministry of Health. These results reinforce the importance of effective support and promotion of breastfeeding as the focus of the nursing team.